2013
DOI: 10.2146/ajhp120634
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and outcomes of patients treated with dabigatran: Pharmacist-managed anticoagulation clinic versus usual care

Abstract: VA patients treated with dabigatran for nonvalvular atrial fibrillation or flutter and followed by a pharmacist-managed ACC did not differ significantly from similar patients receiving UC in the proportion adherent with dabigatran therapy or in the frequency of minor or major bleeding episodes. Thromboembolic events and strokes were absent in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 15 publications
0
34
0
4
Order By: Relevance
“…10 Another study found that anticoagulant clinic patients were more likely to have medication possession ratio (MPR) values of Z80% (considered to be good adherence) on dabigatran at the end of a three-month period than the usual care group. 11 In spite of existing dabigatran research, adherence for this new anticoagulant agent varies among studies and remains sparsely documented.…”
Section: Medication Adherencementioning
confidence: 99%
“…10 Another study found that anticoagulant clinic patients were more likely to have medication possession ratio (MPR) values of Z80% (considered to be good adherence) on dabigatran at the end of a three-month period than the usual care group. 11 In spite of existing dabigatran research, adherence for this new anticoagulant agent varies among studies and remains sparsely documented.…”
Section: Medication Adherencementioning
confidence: 99%
“…The study duration ranged between 3 ( Lee et al, 2013) and 32 (Forslund et al, 2016) months and the data collection method involved patients or national databases. The nine prospective cohort studies were conducted in seven (countries (the UK, the US, Denmark, New Zealand, China, Taiwan, and Germany).…”
Section: Resultsmentioning
confidence: 99%
“…The study duration ranged from 10 ( Thorne et al, 2014) to 23 (Gorst-Rasmussen et al, 2015) months and the sample sizes ranged from 150 (Hu et al, 2015) to 27,514 (Martinez et al, 2016) subjects. The data collection method involved electronic medical record reviews (Donaldson and Norbeck, 2013;Lee et al, 2013;Cutler et al, 2014;Ho et al, 2014;Monteagudo et al, 2015;Martinez et al, 2016), electronic national database searches Larsen et al, 2013;Graham et al, 2014;Beyer-Westendorf et al, 2015;Chang et al, 2015;Gorst-Rasmussen et al, 2015;Hu et al, 2015;Chan et al, 2016;Forslund et al, 2016;Nishtala et al 2016), questionnaires (Thorne et al, 2014;Hu et al, 2015), and a reporting system (Andreica and Grissinger, 2015). The settings of these studies were in hospitals, primary care centres, or both.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations